Penerapan Pembelajaran Berdiferensiasi Berdasarkan Gaya Belajar untuk Meningkatkan Hasil Belajar Matematika Siswa pada Materi Aritmatika Sosial di Kelas VII SMP Negeri 7 Kotamobagu - Manangin, Guslawati; Pomalato, Sarson W.; Oroh, Franky A. (Universitas Sultan Ageng Tirtayasa, 2025)
This study aims to improve students' mathematics learning outcomes on the topic of Social Arithmetic through the implementation of a differentiated instruction model based on learning styles. The research was conducted as a Classroom Action Research (CAR) in Class VII-A of SMP Negeri 7 Kotamobagu during the 2024/2025 academic year. The background of the study highlights low student achievement and limited classroom engagement, primarily caused by monotonous teaching methods and the lack of attention to students’ individual learning styles. Differentiated instruction provides an approach that adjusts the learning process, content, and product according to students' needs, interests, and learning styles. The study was carried out in two cycles, each consisting of planning, action, observation, and reflection phases. Data were collected through teacher and student activity observation sheets and mathematics achievement tests. The results indicate that implementing differentiated instruction based on learning styles effectively increased student engagement and learning outcomes. The percentage of students achieving mastery learning improved significantly from the first to the second cycle. Therefore, this instructional model is effective in enhancing students’ mathematics learning outcomes in the topic of Social Arithmetic.